MEMAKNAI TANDA-TANDA BAHASA DI RUANG PUBLIK DALAM PERSPEKTIF KORTA & PERRY - R. Kunjana Rahardi (Kantor Bahasa Kalimantan Timur, 2023)
The purpose of this research is to describe the manifestation of the meaning and function of the linguistic landscape in the political year in the perspective of Korta & Perry's critical pragmatics. This study applies a phenomenological approach with a qualitative descriptive method. The research data is in the form of snippets of text in which there are signs of language that contain meaning and function as a linguistic landscape in the political year. Sources of substantive data for this research are texts which contain research data as mentioned above. The source of locational data for this research is social media on various platforms that were present around the time of the implementation of this research. Data was collected by applying the observation method to data sources that could potentially contain research data. This listening method is applied with techniques, both basic and advanced in nature, especially reading and note-taking techniques. The results of reading and recording are then identified, classified, and typified. Data analysis was carried out by applying the method of analysis of equivalents, especially contextual equivalents. Such a contextual equivalent analysis is carried out based on the context of the situation which accompanies the emergence of data on language signs in the form of the linguistic landscape. The results of this linguistic landscape research in a critical pragmatic perspective are presented as follows: (1) conveying informational meaning, (2) conveying symbolic meaning, (3) conveying ideological meaning, (4) conveying the meaning of socio-political struggle, (5) conveying the meaning of struggle justice, and (6) conveying the meaning of the struggle for truth.